Influence of hyperelastic properties on the assessment of atherosclerotic plaque vulnerability by inverse analysis. - Latorre Molins, Álvaro Tomás; Peña Baquedano, Estefanía; Martinez Barca, Miguel Ángel (Jornada de Jóvenes Investigadores del I3A, 2023)
Atherosclerotic plaque rupture is one of the leading causes of death worldwide. Therefore, a correct mechanical characterization of its tissues would allow an estimation of its vulnerability. In this work, we present a theoretical methodology to obtain the hyperelastic behavior of the plaque tissues and the zero-pressure geometry.